Caregiver Quality of Life After Cochlear Implantation in Older Adults. Issue 2 (February 2022) - Aylward, Alana; Gordon, Steven A.; Murphy-Meyers, Morganne; Allen, Chelsea McCarty; Patel, Neil S.; Gurgel, Richard K.
Abstract : Objective: To evaluate factors affecting quality of life (QOL) in caregivers of older cochlear implant (CI) recipients. Study Design: Cross-sectional survey. Setting: Academic medical center. Patients: Adults over age 65 receiving CI between July 13, 2000 and April 3, 2019. Interventions: Cochlear implantation. Main Outcome Measures: Linear regression models for caregiver QOL measured by Significant Other Scale for Hearing Disability (SOS-HEAR), with independent variables: caregiver role, patient gender, 11 factor modified frailty index (mFI), duration of hearing loss, hearing aid use, age at surgery, time since surgery, change in pure tone average (PTA), processor input type and Nijmegen Cochlear Implant Questionnaire (NCIQ). Correlations between SOS-HEAR and patient speech recognition scores. Results: Questionnaires were mailed to all 294 living CI recipients. Seventy-one caregivers completed the questionnaire. Only patient gender and mFi were significant predictors of caregiver QOL on both univariate ( p  ⩽ 0.001, β= −20.26 [95% confidence interval –30.21, –10.3]; 0.005, –0.72 [–1.20, –0.23], respectively) and multivariate ( p  = 0.005, β = –20.09, –33.05 to –7.13; 0.003, –0.93 [–1.50, –0.37]) analysis, where caregivers of female patients with lower mFI (better health) had better QOL scores. Caregiver QOL was significantly associated with patient's change in PTA and self-reported QOL scores on univariate ( p  = 0.041, β = 0.52 [0.08, 0.96]; 0.024, –0.27 [–0.52, –0.02]) but not multivariate analysis. Time since CI was significant only on multivariate analysis (0.041, –0.17 [–0.33, –0.01]). Caregiver QOL did not correlate with patient speech recognition scores. Conclusions: Higher QOL scores were found among caregivers of healthier, female CI recipients. Patient hearing measurements did not correspond with better caregiver QOL.